Early Christian attitudes to war, violence and military service - Iosif, Despina (Gorgias studies in classical and late antiquity ;, 2013)
The early Christians were not of one mind when it came to war, violence and military service. There was a bewildering variety of opinion as to how they understood their place in the world. It seems however that generally they did not stand apart from society. On the contrary, they were happy to integrate and conform and they often accepted war and service in the army as activities which did not raise specific ethical problems.